Psychophysical Differences in Ventilatory Awareness and Breathlessness between Athletes and Sedentary Individuals - Faull, Olivia K.; Cox, Pete J.; Pattinson, Kyle T. S. (Frontiers in Physiology, 2016)
Purpose: Breathlessness is a complex set of symptoms that are comprised of both sensory and affective (emotional) dimensions. While ventilation is now understood to be a potential limiter to performance in highly-trained individuals, the contribution of breathlessness-anxiety in those nearing maximal ventilation during intense exercise has not yet been considered as a limiter to performance. Methods: In this study we compared the physiology and psychology of breathlessness in 20 endurance athletes with 20 untrained age- and sex-matched sedentary controls. Subjects completed baseline spirometry and anxiety questionnaires, an incremental exercise test to exhaustion and a steady-state hypercapnic ventilatory response test, with concurrent measures of breathlessness intensity and breathlessness anxiety. Results: Compared with sedentary subjects, athletes reported equivalent breathlessness intensity but greater breathlessness anxiety at maximal exercise (athletes vs sedentary (mean(±SD)): breathlessness intensity (0-100%) 80.7 (22.7) vs 72.5 (17.2), p = 0.21; breathlessness anxiety (0-100%), 45.3 (36.3) vs 22.3 (20.0), p = 0.02). Athletes operated at higher proportions of their maximal ventilatory capacity (MVV) (athletes vs sedentary (mean ventilation (±SD) (% MVV)): 101.6 (27.2) vs 73.7 (30.1), p = 0.003). In the athletes there was a positive linear correlation between ventilation and breathlessness score during the hypercapnic challenge that was not observed in the sedentary controls. Conclusion: The results of this study indicate that whilst operating at high proportions of maximal ventilation, breathlessness anxiety becomes increasingly prominent in athletes. Our results suggest that ventilatory perception pathways may be a target for improved athletic performance in some individuals.